Penerapan Standar Mutu SNI 3021-1992 Edisi ke-1 (Satu) Dalam Prosedur Uji Kinerja Termal Sistem Pemanas Air Tenaga Surya (PATS) - Noor Fachrizal (Institut Teknologi Indonesia, 2021)
The solar water heater (SWH) testing laboratory (LPPATS-B2TKE) has been able to serve commercial product testing based on SNI 3021-1992 1st Edition. Development of test procedures needs to be improved in order to complement the ability to test all parameters contained in the SNI standard. The SWH system performance testing procedure is implicitly described in the form of tables and formulas, so that it needs to be detailed to be implemented in the test. Adopting the SNI thermosiphon procedure, by calculating the daily heat gain, this procedure can produce SWH daily efficiency parameters, which can be used to predict the annual SWH heat gain, PATS product classification, and solar fraction. The results of testing this procedure on a SWH unit with a capacity of 150 liters and a collector area of ​​1.97 m2 for 19 days, obtained daily efficiency in the range of 39.13% to 47.61% in daily radiation between 3.66 - 5.82 kwh/m2, prediction of annual heat gain of 1370, 87 kWh, 75% solar fraction, and prediction of annual heat gain classification of 2783.49 kWh, placing this tested specimen in class III based on SNI standards.